Armenia : Poverty Assessment, Volume 3. Technical Notes and Statistics - World Bank (Washington, DC, 2013)
This report reviews poverty in Armenia in 2001, and examines the most recent trends covering the 1998/99 to 2001 period. It looks at the determinants of poverty, and analyzes linkages between economic growth, sector policies and poverty. The findings are based on two rounds of the Armenia Integrated Living Conditions Survey (ILCS), one carried out in 1998/99, and the other in 2001. The report has contributed to the development of Armenia's national strategy for growth and poverty reduction. Poverty is high in Armenia, with an estimated 48 percent of the population below the poverty line in 2001. Despite some 20 percent still living in extreme poverty, there has been nonetheless, a significant decline in poverty, as poverty incidence dropped by 12 percent, and extreme poverty incidence by 25 percent from their respective levels in 1998/99. There is a strong correlation between poverty and low educational attainment, while the unemployed and non-participants in the labor market, face the highest poverty risk, depth and severity of poverty. In rural areas, poverty is positively correlated with the size of landholdings. The drop in poverty reflects a decline in urban poverty since 1998/99. Rural poverty has increased slightly. Yerevan, the capital and largest urban area in Armenia, registered the most significant reduction in poverty, as poverty incidence there dropped by 23 percent and extreme poverty by over a third, to 45 percent and 20 percent, respectively. While poverty in other urban areas also decreased, their poverty incidence still remains above the national rate, at 52 percent. Poverty incidence is now roughly the same in urban and rural areas, 48.5 percent and 47.9 percent, respectively. Government policies aimed at macroeconomic stability and diversification of the economy should be pursued, and, recommendations further include increasing the level and quality of education, and ensuring better health for all, critical to reduce poverty. Concerning social protection, consideration should be given to expanding it to cover most of the extremely poor, as well as refining targeting mechanisms.